Improving mass spectrometry analysis of protein structures with arginine-selective chemical cross-linkers - Alexander X. Jones (Nature Portfolio, 2019)
Cross-linking mass spectrometry can provide insights into protein structures and interactions but its scope depends on the reactivity of the cross-linker. Here, the authors develop Arg-Arg and Lys-Arg cross-linkers, which provide structural information elusive to the widely used Lys-Lys cross-linkers.